A ground state solution for an asymptotically periodic quasilinear Schrödinger equation. (15th September 2017) - Xue, Yan-Fang; Liu, Jiu; Tang, Chun-Lei
Abstract: This article is concerned with the existence of positive ground state solutions for an asymptotically periodic quasilinear Schrödinger equation. By using a change of variables, the quasilinear problem is transformed into a semilinear one. Then, we use a Nehari-type constraint to get the existence result.